Evaluation of Sport Federation Management Models through Competing Values Approach - Maryam Esmaeilimotlagh, Maryam Asadollahi Kheirabadi,; Jokar, Solmaz; Alizadeh, Fereshteh; Basiri, Zeinab (Opción, 2019)
The aim of this research is to study and analyze the effectiveness models in selected sports federations. The current research is an exploratory survey that has studied the organizational effectiveness factors of Iran’s sports federations with a correlational method. The results showed that volleyball, taekwondo, basketball, weightlifting, wrestling, and handball federations had the highest mean of organizational effectiveness, respectively. In conclusion, supporting and rewarding the athletes mentally and physically, providing adequate training centers, and paving the way for their education are among the activities that lead to the satisfaction of elite athletes.